Impact of Exposure Conditions on the Morphology of Polyethylene by Compact NMR. Issue 1 (20th April 2018) - Teymouri, Yadollah; Adams, Alina; Blümich, Bernhard
Abstract : Today many polyethylene (PE) products are employed in long‐term applications that require the use of elevated temperatures and/or contact with different solvents. Both the exposure to heat and solvents can result in morphological changes, compromising the mechanical stability of the material. Disentangling morphological changes induced by either type of exposure and understanding their combined effect is crucial for establishing reliable structure‐property relationships. This, in turn, requires sensitive analytical methods that can probe the complex morphology of PE both in the laboratory and on site. Among existing analytical methods, NMR with compact devices have recently become a key analytical tool for the detailed morphological characterization of a variety of solid polymers including PE. This current work reviews the potential of compact NMR for monitoring and quantifying morphological changes in PE exposed to the aforementioned external conditions. To prove the reliability of compact proton NMR relaxation measurements, the results are compared with data from conventional high‐field proton wide‐line NMR spectroscopy, DSC, and FTIR spectroscopy. It could be shown that simple, static proton relaxation measurements garner detailed information about the exposure‐induced morphological changes through the quantification of phase composition and chain dynamics. Moreover, the NMR method has a key advantage over other methods, because the chain mobility of the soft amorphous phase is a very sensitive microscopic parameter under exposure conditions. The various presented examples and the good agreement of the NMR results with those of other analytical methods show that low‐field NMR is a promising option for in‐situ aging studies.